Faktor Pendukung Peningkatan Pendapatan Usaha Mikro Kecil Menengah - Sadira, Alvita; Lukita, Carolyn; Trisyanto, Ade (Gorontalo Accounting Journal, 2025)
This study aims to provide empirical evidence regarding the influence of business capital, number of workers, accounting comprehension, and financial technology on the income growth of Micro, Small, and Medium Enterprises (MSMEs) in West Karawang District. This quantitative research with a descriptive approach utilized primary data collected through questionnaires distributed to MSME actors in the region. The research sample consisted of 105 respondents selected using a purposive sampling technique. Data were analyzed using multiple linear regression analysis. The results indicate that, partially, business capital, number of workers, and financial technology have a positive and significant effect on MSME income, while accounting comprehension does not have a significant impact. Simultaneously, all four variables are shown to influence MSME income growth.